2019
DOI: 10.1037/drm0000110
|View full text |Cite
|
Sign up to set email alerts
|

The role of dreams of ads in purchase intention.

Abstract: While highlighting the significance of exposure to ads to explain consumer behavior, extant literature has so far disregarded the potential impact of dreams. Linking the current-concerns theory and the model of cognitive response to advertising, this study focuses on the impact of dreaming of ads on purchase intentions. To test the 3 research hypotheses proposed, a quantitative study was conducted with Iranian consumers, using individuals' retrospective self-assessment on the 3 variables of the study: exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 42 publications
(67 reference statements)
3
13
0
Order By: Relevance
“…Previous research shows that exposure to ads, dreams of ads, and purchase intentions influence each other. Previous research confirmed that Exposure to Ads has a positive impact on Purchase Intention, which also has direct and indirect effects on Dreams of Ads (Mahdavi, Fatehi Rad and Barbosa, 2019). Advertising is a dreamlike structure.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Previous research shows that exposure to ads, dreams of ads, and purchase intentions influence each other. Previous research confirmed that Exposure to Ads has a positive impact on Purchase Intention, which also has direct and indirect effects on Dreams of Ads (Mahdavi, Fatehi Rad and Barbosa, 2019). Advertising is a dreamlike structure.…”
Section: Introductionmentioning
confidence: 83%
“…So in this study, socioeconomic factors are used as a consideration in the form of Price variables. In the two previous studies (Forest, 2016;Mahdavi, Fatehi Rad and Barbosa, 2019), the object of research is still too Fara Hajar Puspita Putri Tantri Yanuar Rahmat Syah 282 broad. The thing of research taken is consumers in a country in general.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations